COMPOSITION OF TYPE AND WEIGHT OF HARVEST CATCH IN LALANG VILLAGE, SUNGAI APIT DISTRICT, SIAK REGENCY - Faroza, Yufi; Bustari, Bustari; Isnaniah, Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABCTRACTThis research was carried out in December 2020 in Lalang Village, Sungai Apit District, Siak Regency. This study aims to determine the composition of the type and weight of the catch and the strength of the current relationship with the catch operated in Lalang Village, Sungai Apit District, Siak Regency. The research method used is the survey method. The data that has been obtained after being tabulated is then analyzed descriptively. The catch obtained by the pengerih fishing gear consisted of 8 species, namely lomek fish (Harpodon nehereus), pomfret (Colossoma macropum), thorn fish (Arius thalasius), gulamo fish (Bahaba poly kladieous), exorbitant fish (Nematalosa come), turtle fish (Eleutheronema tetradactylum), ringworm (Llisha elongata) and shrimp (Metapenaeus monocerous). While the analysis of the strength of the relationship between catches and current velocity in Lalang Village, current velocity has a strong relationship with the number of catches produced by the fishing gear as seen from the coefficient of determination of the fishing gear, which is 0.99 (0.80-1.00) . It can be concluded that the current is very influential on the catch obtained by fishing gear in Lalang Village, Sungai Apit District, Siak Regency. Keywords: Fishing gear, simple linear, Lalang Village